Dimensions de la diversité des maïs indigènes au Mexique - Cecilio Mota Cruz (Revue d'ethnoécologie)
Maize is currently the most widely produced cereal in the world and it was domesticated in Mexico, approximately 10,000 years ago, from a wild grass known as teosinte. In Mexico, it became highly diversified, spreading throughout the American Continent and in the 6th century it reached various latitudes of the Old World. In Mexico, farmers, their families and communities maintain an enormous diversity of native maize, which they cultivate in a wide range of environmental conditions mainly for food uses. Maize constitutes the fundamental source of food for the population and a wide diversity of culinary uses and cultural expressions have been developed around it. Some aspects of this diversity in Mexico are discussed here.